The appeals process: An empirical assessment - Kai Hüschelrath; Florian Smuda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The appeals process - whereby the losing party of an administrative or judicial decision can seek reconsideration of their arguments before a higher institution - is an important mechanism to correct legal errors and to improve existing laws and regulations. We use data of 467 firm groups that participated in 88 cartels convicted by the European Commission between 2000 and 2012 to study both the characteristics of firm groups filing an appeal and the factors that determine their successfulness in terms of fine reduction. Applying discrete choice models and a two-stage hurdle model, we find that while some characteristics - such as the size and financial condition of the firm group or the clarity of fine guidelines - only affect the probability to file an appeal, other factors such as the size of the fine imposed in connection to characteristics as ringleader, repeat offender or leniency applicant influence both the probability and the success of an appeal. We take our empirical results to derive conclusions for both firms and public policy makers.
urn:nbn:de:bsz:180-madoc-370942
Keywords: K21; K41; K42; L41; 330; Law and Economics; appeals; antitrust policy; cartels; European Union